Ethical decision-making dynamics: insights from professional accountants - Ishwara P; Naod Mekonnen (Cogent Business & Management, 2024)
This study examines the relationships between the components of ethical decision-making and the factors that contribute to the ethical decision-making of professional accountants. Survey data from 309 professional accountants was analyzed using partial least squares structural equation modeling. The study found positive relationships among moral recognition, moral judgment, and moral intent. Moral judgment mediates the relationship between moral recognition and moral intent in ethical decision-making. The study also found that laws and professional codes, moral philosophies, intrinsic religious orientation, and social responsibility influenced ethical decision-making. However, peer group pressure did not predict moral judgment among professional accountants. This study provides implications for considering the mediating role of moral judgment in the ethical decision-making process. To improve ethical decision-making among professional accountants, understanding the influences and relationships of other factors is crucial in an ethical setting.
Keywords: 650; Moral recognition; moral judgment; moral intent; ethical decision-making factors; professional accountants